The Impact of Procedural Justice on Employee Intention to Stay in Nepalese Insurance Companies: Exploring the Mediating Role of Affective Commitment - Subedi, Dhruba; Dilli Ram Bhandari, (Technium Social Sciences Journal, 2024)
Procedural justice fosters the perceptions of fairness and support within the organization ensuring that all employees are treated equitably and transparently. It supports employees to stay a long term by creating a sense of fairness and trust in organizational processes, leading to higher job satisfaction and emotional commitment. This study examines the influence of procedural justice on intention to stay of employees within the Nepalese insurance companies, emphasizing the mediating role of affective commitment. To achieve the stated objective, data were collected from the primary source using a structured questionnaire administered through random sampling technique. The respondents comprised 298 employees of insurance companies working in different positions. The Smart PLS 4.0 was used to analyze the structural relationships within the proposed theoretical model. The findings of this study validated the set hypotheses that procedural justice has positive and significant effect on the intention to stay of the employees in Nepalese insurance sectors. The findings indicate that fair and transparent organizational procedures significantly enhance employees' emotional attachment to their companies, thereby increasing their intention to remain. By fostering perceptions of fairness, insurance companies can strengthen affective commitment, ultimately reducing turnover intentions and promoting long-term organizational stability. This research highlights the importance of procedural justice in retaining a committed and loyal workforce within the Nepalese insurance sector.